2019
DOI: 10.1002/pmrj.12121
|View full text |Cite
|
Sign up to set email alerts
|

Physical Function and Pre‐Amputation Characteristics Explain Daily Step Count after Dysvascular Amputation

Abstract: Background People with dysvascular lower limb amputation (LLA) achieve one‐third of the recommended steps per day and experience severe disability. Although physical function improves with rehabilitation after dysvascular LLA, physical activity remains largely unchanged, and factors contributing to limited daily step count are unknown. Objectives To identify factors that contribute to daily step count after dysvascular LLA. Design Cross‐sectional, secondary data analysis. Setting Outpatient rehabilitation faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 74 publications
(155 reference statements)
1
16
0
Order By: Relevance
“…Historically, psychosocial concerns have had limited focus during rehabilitation, with physical function as the primary target of conventional rehabilitation following both traumatic and dysvascular LLA 2‐4 . Findings from the final regression model in this study reinforce prior evidence of association between perceived physical function and rehabilitation outcome 11,15 . Specifically, for every one‐point increase in perceived functional capacity (PEQ‐MS; 0: unable to 4: no difficulty), the disability score (WHODAS 2.0) was 5 points lower, indicating lower disability.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Historically, psychosocial concerns have had limited focus during rehabilitation, with physical function as the primary target of conventional rehabilitation following both traumatic and dysvascular LLA 2‐4 . Findings from the final regression model in this study reinforce prior evidence of association between perceived physical function and rehabilitation outcome 11,15 . Specifically, for every one‐point increase in perceived functional capacity (PEQ‐MS; 0: unable to 4: no difficulty), the disability score (WHODAS 2.0) was 5 points lower, indicating lower disability.…”
Section: Discussionsupporting
confidence: 70%
“…Further, a longstanding bias towards research focused on young and relatively healthy people with LLA has limited the generalizability of findings towards older people with LLA with multiple comorbid conditions, 8 including those who use a prosthesis for locomotion. Although there is a growing body of evidence highlighting the significance of complicating factors (eg, multiple comorbid conditions), there continues to be a lack of clarity about etiology‐specific influences (eg, traumatic, dysvascular) on rehabilitation outcomes for people of similar age and time since LLA who use a prosthesis beyond 1 year post‐LLA 9‐15 . Theoretical underpinnings suggest factors ranging from age, chronic disease, adjustment, and social functioning may influence etiology‐specific differences in rehabilitation outcomes within the first year of LLA, regardless of prosthesis use for locomotion 14 .…”
Section: Introductionmentioning
confidence: 99%
“…62,63 The time course of physical activity recovery for patients with nontraumatic LLA is unique, as they require extended recovery times compared to patients with LLA from other etiologies, due to vascular and medical comorbidity. 64 Previous studies in nontraumatic LLA have found accelerometer-based average daily step counts to be very low, 9,11 equating to less than one-third of the recommended daily steps for people with disabilities. 59 For example, average daily steps for people within the first 6 months after LLA have been measured at 1721 (1524) steps/d [mean(SD)].…”
Section: Discussionmentioning
confidence: 99%
“…10 It is possible that such low physical activity and high disability are associated with chronic behaviors that predate the need for amputation. 11 Current clinical practice guidelines for rehabilitation describe a comprehensive approach, including mobility training and community reintegration after LLA. 12 Conventional LLA rehabilitation guidelines encourage increasing free-living physical activity through resistance exercise, mobility training, cardiovascular exercise, and other specific functional exercises.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation